Torus Knot Polynomials and Susy Wilson Loops - Giasemidis, Georgios; Tierz, Miguel (Letters in mathematical physics, 2014)
We give, using an explicit expression obtained in (Jones V, Ann Math 126:335, 1987 ), a basic hypergeometric representation of the HOMFLY polynomial of ( n , m ) torus knots, and present a number of equivalent expressions, all related by Heine’s transformations. Using this result, the ( m , n ) ↔ ( n , m ) symmetry and the leading polynomial at large N are explicit. We show the latter to be the Wilson loop of 2d Yang–Mills theory on the plane. In addition, after taking one winding to infinity, it becomes the Wilson loop in the zero instanton sector of the 2d Yang–Mills theory, which is known to give averages of Wilson loops in N = 4 SYM theory. We also give, using matrix models, an interpretation of the HOMFLY polynomial and the corresponding Jones–Rosso representation in terms of q -harmonic oscillators.